Levodopa and the feedback process on set-shifting in Parkinson's disease - Au, Wing Lok (2013)
To study the interaction between levodopa and the feedback process on set-shifting in Parkinson's disease (PD). Methods: Functional magnetic resonance imaging (fMRI) studies were performed on 13 PD subjects and 17 age-matched healthy controls while they performed a modified card-sorting task. Experimental time periods were defined based on the types of feedback provided. PD subjects underwent the fMRI experiment twice, once during “off” medication (PDoff) and again after levodopa replacement (PDon). Results: Compared with normal subjects, the cognitive processing times were prolonged in PDoff but not in PDon subjects during learning through positive outcomes. The ability to set-shift through negative outcomes was not affected in PD subjects, even when “off” medication. Intergroup comparisons showed the lateral prefrontal cortex was deactivated in PDoff subjects during positive feedback learning, especially following internal feedback cues. The cortical activations were increased in the posterior brain regions in PDoff subjects following external feedback learning, especially when negative feedback cues were provided. Levodopa replacement did not completely restore the activation patterns in PD subjects to normal although activations in the corticostriatal loops were restored. Conclusion: PD subjects showed differential ability to set-shift, depending on the dopamine status as well as the types of feedback cues provided. PD subjects had difficulty performing set-shift tasks through positive outcomes when “off” medication, and showed improvement after levodopa replacement. The ability to set-shift through negative feedback was not affected in PD subjects even when “off” medication, possibly due to compensatory changes outside the nigrostriatal dopaminergic pathway.